MBus: An ultra-low power interconnect bus for next generation nanopower systems - Pannuto, Pat; Lee, Yoonmyung; Kuo, Ye-Sheng; Foo, ZhiYoong; Kempke, Benjamin; Kim, Gyouho; Dreslinski, Ronald G.; Blaauw, David; Dutta, Prabal (Proceedings - International Symposium on Computer Architecture, 2015)
As we show in this paper, I/O has become the limiting factor in scaling down size and power toward the goal of invisible computing. Achieving this goal will require composing optimized and specialized-yet reusable-components with an interconnect that permits tiny, ultra-low power systems. In contrast to today's interconnects which are limited by power-hungry pull-ups or high-overhead chip-select lines, our approach provides a superset of common bus features but at lower power, with fixed area and pin count, using fully synthesizable logic, and with surprisingly low protocol overhead.